THE CORRELATION BETWEEN STUDENTS’ PERSONALITY AND STUDENTS’ SPEAKING SKILL - Desi Surlitasari Dewi; Safnidar Siahaan; Novriza Nizami Putri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The objective of the study is to find out whether any correlation between students’ personality and students’ speaking skill. The research design was correlational research. This research has two variables, the students’ personality was treated as an independent variable (X), and students’ speaking skill was treated as dependent variable (Y). The sampling technique was probability sampling technique with cluster sampling. The sample in this research was forty students of VIII A Class. The instruments to check the students’ personality was Myers Briggs Type Indicator (MBTI) Personality Test while the instrument to measure the students’ speaking skill was a speaking test in oral presentation of a short and simple recount text related to students’ personal experiences. After testing the validity and reliability, the researcher distributed the test. The researcher analyzed the correlation by using Point-Biserial Correlation. The result showed that the rcount was 51200. The ttable with sample 38 (N-2) at the 5% significance level were 2.024. It means that rcount is higher than ttable and Ho is rejected and Ha is accepted. The research found that there was significant correlation between Students’ Personality and Students’ Speaking Skills at second grade students of SMP Negeri 50 Batam.